Correlation of estimated fetal weight by ultrasound and birth weight in low risk pregnancy: a prospective study - Marla, Shreesha; Ganiga, Pradeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Sonographic fetal weight estimation is an important aspect of antenatal care. It is one of many important factors used to determine when and how to terminate pregnancy. This study was therefore carried out to sonographically estimate fetal weight with actual birth weight, to analyze various demographic parameters with birth weight and thus predict neonatal outcomes. Aim of the study was to correlate estimated fetal weight by ultrasound and actual birth weight in all low-risk antenatal women attending regular antenatal check-ups at tertiary care center Methods: This was time bound prospective study, was conducted in pregnant women undergoing antenatal check-up in a tertiary care center from April 2022 to August 2022. During antenatal check-up, the subject was advised to undergo ultrasound imaging at 32-36 weeks and at term to look for BPD, AC, HC, FL, EFW. Clinically estimated fetal weight noted. Following delivery of baby, birthweight is recorded. Estimated fetal weight and actual birth weight are correlated and neonatal outcomes assessed. Results: As per the study sonographically estimated fetal weight at 32-36 weeks and at term, clinically estimated fetal weight correlated positively with actual birth weight. Conclusions: The statistics as per this study conducted in tertiary care centre in mangalore could be applied to Indian population, which may aid obstetricians in planning the mode of delivery, improve pre-labour counselling and efficient management of antenatal mother and large babies. Clinically estimated fetal weight could be used as a diagnostic tool sufficient to manage labour and delivery efficiently in low resource setting.